Energy cost and energy sources of ball routine in rhythmic gymnasts - Guidetti, L.; Baldari, C.; Capranica, L.; Persichini, C.; Figura, F. (International Journal of Sports Medicine, 2000)
The energy cost and the different energy sources of competitive rhythmic ball-routines were assessed in nine young elite rhythmic gymnasts (13-16 years of age). The overall energy requirement of ball exercise (VO2eq) was obtained by adding the amount of VO2 during exercise above resting (VO2ex) to the VO2 up to the fast component of recovery (VO2al) and to the energy equivalent of peak blood lactate accumulation (VO2la-) of recovery. The lactate (La) curve up to 25 minutes of recovery always showed La peaks at 3 min after exercise (4.0 +/- 0.4 mmol/l) and values still above rest at 25 min (2.3 +/- 0.5 mmol/l). Although ball routines were short in duration (90 s), the metabolic power requirement was 1.1 times higher than the subject's VO2max. The energy cost (VO2eq) amounted to 81 +/- 5 ml x kg(-1). Higher fractions of VO2eq were VO2ex 49% and VO2al 42%, while the remaining 9% was due to VO2la-. The aerobic source resulted in the most utilized system due to the subjects' high VO2max (52.7 ml x kg(-1) x min(-1)) and anaerobic threshold (LT = 84.4%). The HR and the peak lactate values of ball routine were similar to the values recorded at LT step during treadmill test. Although the HR and VO2 values were significantly correlated (during pre-exercise, exercise, and fast recovery), the exercise intensity derived from HR Kanvonen method during ball routine did not correspond to the % of VO2max.